Investigating Famous Quotes of World Figures in Improving Students’ Studying Motivation at AMIK JTC Semarang - Yessi Aprilia Waluyo; Tatas Transinata; Enggar Dhian Pratamanti; Wiwit Rahma Wati; Gde Brahupadhya Subiksa (Universitas Cokroaminoto Palopo, 2025)
Language is the communication tool which also has meanings. Language meanings can be taken from direct speech acts and indirect speech acts. Furthermore, those meanings can give people’s motivation. Famous quote is one of the ways to increase the motivation. Famous quotes can be from various languages. They consist of words, phrases and sentences which have influential and worthed messages and meanings which are useful to increase studying motivation. AMIK JTC Semarang uses famous quotes in the form of posters to influent the positive mindset and attitude of students in achieving the goals. The purposes of this study are to investigate and analyse whether famous quotes of world figures can improve the studying motivation of students or not and which famous quotes of world figures have strong, enough and weak influences that can improve the studying motivation of students based on the students’ perceptions in the form of converted numbers. The method used in this study is quantitative method. This study is based on the results of analysis by using Likert scales and counted and converted by using three box method and SPSS. There are 44 famous quotes of world figures in the form of posters at AMIK JTC Semarang. Most of 44 famous quotes get high perceptions from the students who have ever seen and known them. It means that most of the students recognize and agree that 44 famous quotes of world figures at AMIK JTC Semarang can give their studying motivations to reach their goals and success. However, it can be summarized that there are 8 famous quotes which have strong influence in improving the student’s studying motivation, 24 famous quotes with enough influence, and 12 famous quotes with low or weak influence in improving the studying motivation of students.